Integrating Qiaopi into University Patriotism Education: Enhancing Cultural Awareness and Moral Values in a Globalized Era - Shishi Chen (Ilmu Inovasi Nusantara, 2024)
This study investigates the potential of incorporating Qiaopi, the traditional postal system used by overseas Chinese, into university patriotism education as a means to strengthen students' moral and cultural values. Qiaopi, a significant element of cultural heritage, encapsulates values such as integrity, patriotism, filial piety and perseverance, which are essential for fostering a well-rounded moral compass among students. By exploring Qiaopi as both a historical artifact and a medium for cultural transmission, this research highlights its unique ability to enhance students' cultural awareness and deepen their sense of patriotism. Using a qualitative methodology, the study involves a analysis of existing literature on Qiaopi. The aim is to understand how Qiaopi's rich cultural significance can be leveraged in modern educational settings to cultivate a stronger sense of national identity among students. The findings reveal that Qiaopi, when integrated effectively into the curriculum, can serve as a valuable educational resource that not only teaches historical and cultural knowledge but also instills important moral values. The study underscores the importance of optimizing the use of Qiaopi in educational programs. This can be achieved by developing digital resources that make Qiaopi more accessible, organizing cultural research activities, and promoting its integration into classroom instruction. Additionally, creating a campus environment that actively supports cultural heritage can further amplify the impact of Qiaopi-based education. Ultimately, this research advocates for a more dynamic and culturally enriched approach to patriotism education that better prepares college students to address the complexities of the globalized world while maintaining a strong moral foundation